Bending performance of glubam beams made with different processes. Issue 2 (January 2019) - Li, Z; Yang, GS; Zhou, Q; Shan, B; Xiao, Yan
This article presents experimental testing results designed to obtain physical and mechanical properties of glued laminated bamboo (glubam) beams. Two types of glubam beams made with different pre-processed plybamboo boards were tested. One type glubam beam specimens were made with thin layer bamboo strips of about 2 mm thick, and the other were manufactured with thick layer bamboo strips of about 5–6 mm. Test results of the full-scale beams show that the behavior of the glubam beams was elasto-brittle, similar to typical wood-based glulam. The different configurations of bamboo strips have certain influence on the flexural performance of glubam beams, and the mean ultimate capacity of the samples with bamboo strips flatwise is higher than that of edgewise. Based on the experimental results reported herein, the strength capacity equations are proposed for calculating the flexural rigidity and strength capacities of the glubam beams.